News Management Application Development - Muhammad Adryan Syahputra; Rizqa Raaiqa Bintana; Dewi Lestari (IJNMT (International Journal of New Media Technology), 2025)
This study aims to develop a news management application at institution X that has been running previously, into an interactive application that can be used as a means of writing, reviewing and collecting news articles which are then published to daily newspaper pages. The application development model used in this study is the waterfall model. The waterfall model involves stages such as communication, planning, modeling, construction, and deployment. This study succeeded in developing a news management application from the previous version into a new application with the implementation of all its functional requirements. Testing was carried out using the black box method and system usability scale (SUS). The results of the black box test showed that the news management application had successfully carried out all functions correctly and in accordance with expectations. In the SUS test, two measurements were taken, namely before and after development. The SUS score before development was 71.3, while after development it increased to 78.8. This shows an increase in user perception of the usability of the application after development was carried out. Structured work and a clear flow from initiation to end can minimize errors because it has clear details and final descriptions.